Acta pontificia et Decreta Ss. Romanarum Congregationum (F. Pustet, 1909)
Keywords: 2.Damage; Condition: Fair; Religion

Boletim Offical do Governo Da Provincia De Macau (Typografia Mereantil, 1909)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; 2.Damage

L'église Saint-Louis-des-Français de Rome: petit guide du visiteur (Jonquières & Dati, 1909)
Keywords: Guides touristiques et de visite; Rome (Italie) Église Saint-Louis des Francais; Églises Italie Rome (Italie)

Liga de Sancitidade Sacerdotal ou Pia Uniao (Typ. Casa Cath., 1909)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Propaedeutrica Biblica seu Cpmpendium Sue Compendium introductionis criticae et Exgeticae (Ex Officina Libraria, Barigelletti, 1909)
Stamp
Keywords: Fair

Propaedeutrica Biblica seu Cpmpendium Sue Compendium introductionis criticae et Exgeticae (Ex Officina Libraria, Barigelletti, 1909)
Stamp
Keywords: 18.Bookworm; 2.Damage

Savina?, F. , ( Prefacio), Dictionnairetay- Annamite-Francais, Incompleto."Falto o Frontespicio". (1909)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Dictionaries

四史集一: 十卷 (北京救世堂, 1909)

四史集一: 註解 (北京救世堂, 1909)

Annaes da propagação da fé - Associação da Propagação da Fé (Na Typ. de G. M. Martins, 1909)
Keywords: 2.Damage; Condition: Fair; Missões [Periódicos]; Religion

Annaes da propagação da fé - Associação da Propagação da Fé (Na Typ. de G. M. Martins, 1909)
Keywords: 2.Damage; Condition: Fair; Missões [Periódicos]; Religion

Annaes da propagação da fé - Associação da Propagação da Fé (Na Typ. de G. M. Martins, 1909)
Keywords: 2.Damage; Condition: Fair; Missões [Periódicos]; Religion

Les Evangeliques Vie de Jesus- Christ Meditee - Baudo, L'abbe Prosper (Desclee, de Brouboer et Cie, 1909)
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 2.Damage

Un Miracle D'aujourd'hui Discussion Scientifique - Bertrin, Georges (Bureaux et Magasin, 1909)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Compendium Theologiae Dogmaticae - Caesare, Manzoni (Ex Libraria a SS. Corde Jesu, 1909)
Keywords: 1.Conservation 保護; 15.Stain 污漬; Fair

Compendium Theologiae Dogmaticae e Praecipuis Scholasticis antiquis et Modernis redactum - Caesare, Manzoni (Ex Libraria a SS. Corde Jesu, 1909)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Compendium Theologiae Dogmaticae e Praeipuis scholasticis antiquis et modernis redactum - Caesare, Manzoni (Ex Libraria a SS. Corde Jesu, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Compendium Theologiae Dogmaticae e Praeipuis scholasticis antiquis et modernis redactum - Caesare, Manzoni (Ex Libraria a SS. Corde Jesu, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Compendium Theologiae Dogmaticae e Praeipuis scholasticis antiquis et modernis redactum - Caesare, Manzoni (Ex Libraria a SS. Corde Jesu, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Compendium Theologiae Dogmaticae e Praeipuis scholasticis antiquis et modernis redactum - Caesare, Manzoni (Ex Libraria a SS. Corde Jesu, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

De Sacramentis - Christiano Pesch S. J. (Praelectiones dogmaticae, 1909)
stamp of seminario de s. jose macau stamp of bibliotheque de Nazareth
Keywords: 18.Bookworm; Good

La Bienheureuse Jeanne d'Arc, Depeinte par elle-meme - Delarbre, P. Raphael (Imp. Francisc. Missionnaire, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage

Contribuicao para o Estudo da Nosografia de Timor - Filipe de Moraes, J. Antonio (Typ. Mercantil, 1909)

Stambul ou Itinerario d'uma viagem a Constantinopla - Freitas, Senna (Parceria Antonio Maria Pereira, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Centelhas Eucharisticas - Gomes, Antonio, J. (Cruz & Comp, editores, 1909)
Signature
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

The Catholic encyclopedia: an international work of reference on the constitution, doctrine, discipline, and history of the catholic church - Herbermann, Charles George (Robert Appleton Co., 1909)
Keywords: Catholic Church; Catholic Church Dictionaries; Condition: Fair; Dictionaries; Encyclopedias and dictionaries; Hard Cover; Theology; Theology Dictionaries; Église catholique Dictionnaires anglais

The Catholic encyclopedia: an international work of reference on the constitution, doctrine, discipline, and history of the catholic church - Herbermann, Charles George (Robert Appleton Co., 1909)
Keywords: Catholic Church; Catholic Church Dictionaries; Condition: Fair; Dictionaries; Encyclopedias and dictionaries; Hard Cover; Theology; Theology Dictionaries; Église catholique Dictionnaires anglais

Exposition de la Morale Catholique, VII La Loi - Janvier, P. M. A (P. Lethielleux, Libraire-Editeur, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Retraites Pascales 1889-1890 - Le T. R. P. J.-L.-M. Monsabre (P. Lethielleux, 1909)
stamp of biblotheque de Nazareth
Keywords: Good

La Communion, Frequente et Quotidienne - Maillet, L'abbe C. (Aubanel frères, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage

Obras completas do Padre António Vieira. Sermões - Padre Goncalo Alves (Livraria Chardron, 1909)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Religion

Obras completas do Padre António Vieira. Sermões - Padre Goncalo Alves (Livraria Chardron, 1909)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Religion

Obras completas do Padre António Vieira. Sermões - Padre Goncalo Alves (Livraria Chardron, 1909)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Religion

Obras completas do Padre António Vieira. Sermões - Padre Goncalo Alves (Livraria Chardron, 1909)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Religion

Histoire des Papes depuis la fin du Moyen-Age: ouvrage écrit d'après un grand nombre de documents inédits extraits des archives secrètes du Vatican et autres. Tome septième - Pastor, Ludwig von; Poizat, Alfred (Librairie Plon : Plon-Nourrit et Cie, imprimeurs-éditeurs, 1909)
Keywords: 2.Damage; Condition: Fair; History; Léon X (pape; 1475-1521) Activité politique; Papauté Histoire; Religion

Histoire des Papes depuis la fin du Moyen-Age: ouvrage écrit d'après un grand nombre de documents inédits extraits des archives secrètes du Vatican et autres. Tome septième - Pastor, Ludwig von; Poizat, Alfred (Librairie Plon : Plon-Nourrit et Cie, imprimeurs-éditeurs, 1909)
Keywords: 2.Damage; Condition: Fair; History; Léon X (pape; 1475-1521) Activité politique; Papauté Histoire; Religion

Manual de Pedagogía Eclesiástica - Pedro Valls Tarraco, D. (Eugênio Subirana, 1909)

De Deo Creante et Elevante de Deo Fine Ultimo - Pesch, Christiano (Sumptibus Herder, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

De Verbo Incarnato de Beata Virgine Maria de Cultu Sanctorum - Pesch, Christiano (Sumptibus Herder, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Theologia Pastoral, Elementos de Eloquencia Gagrada - Pinto, Antoino Ferreira (Typ. z vopor da Real Officina de S. Jose, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

A Mis Seminaristas - Ramirez, Alfonso M. (Luis Gili, Editor, 1909)
Stamp of St. Joseph Seminary

O Evangelho segundo S. Mattheus - Santanna, Padre (Typographia A Editora, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 2.Damage

Apologia Scientifica da Fe Christa - Senderens, J. B (Typ. da Revista Catholica, 1909)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Nacionalismo e Accao Catholica - Silva, Manuel Abundio (Casa Editora de Antonio Figueirinhas, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 2.Damage

Catechismo Popular Catholico - Spirago, Francisco (Antonio Dourado, 1909)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Nouvelles Meditations Pratiques - Vercruysse, P. Bruno (Societe belge de librairie, 1909)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

A century of Spain and Portugal (1788-1898) - White, G. F. (Methuen, 1909)
Keywords: 1788-1900; 18.Bookworm; 22.stamp; Condition: Poor; Espagne Histoire 1788-1808 (Charles IV); Espagne Histoire 19e siècle; Hard Cover; History; Portugal; Portugal Histoire 1789-1900; Portugal History 1789-1900; Spain; Spain History 19th century; Spain History Charles IV, 1788-1808

Sermoes e Panegyricos do Principe dos Oradores Sagrados - Zocchi, Caetano (Typographia da Revista Catholica, 1909)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

教育雜誌 第九卷第三節 = The Chinese Educational Review Vol. VIIII No.3 - 天, 民 (Commercial Press (商務印書館), 1909)
Keywords: China; Education; Education China Periodicals; Education Periodicals; Periodicals; Éducation Chine Périodiques

中國地理教科書 - 武, 進屠; 陽, 湖莊 (學部審定. 中學堂. 師範學堂用, 1909)